Pekalongan City of Batik: Expression Of Acculturation And Characteristics Diversity: English - Yusril Bariki Yusril; Nur Afifah (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2023)
Cultural issues have become a hot topic of discussion in today's society. The usage of batik and the identity should the young people to experience several acculturation problems. This study tries to explain Pekalongan's identity as a city of batik as well as the significance in it. With the use of literature reviews, analyses, and theories supporting acculturation and batik identity, the method of library research is applied to investigate field data. The results revealed that Pekalongan City is a city of batik, that it is actually known as The World City of batik, and that the current batik designs explain what acculturation and diversity of traits entail. This region is home to six distinct types of batik: Batik jlamprang, which conveys the idea that Muslim culture still upholds each other's friendships and lives in harmony; cement batik, which represents a life that can expand, grow, and blossom into a morewealthy life. Bright moon batik This motif's meaning is that everything will always turn out well or perfectly when it should; Seven different types of batik are a representation of the fusion of Javanese and Chinese cultures. The Seven Shapes motif, which means a manifestation of the many abilities of creatures that are united in themselves, demonstrates the wealth of the Pekalongan region. Batik Liong, which means a symbol of power, and Sawat Batik, which means to safeguard. It is clear that the city of Pekalongan has a pluralistic acculturation character based on the local motifs.